2012
DOI: 10.4103/0019-5545.99540
|View full text |Cite
|
Sign up to set email alerts
|

Neurological soft signs in children with attention deficit hyperactivity disorder

Abstract: Context:Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder with wide repercussions. Since it is etiologically related to delayed maturation, neurological soft signs (NSS) could be a tool to assess this. Further the correlation of NSS with severity and type of ADHD and presence of Specific Learning Disability (SLD) would give further insight into it.Aims:To study neurological soft signs and risk factors (type, mode of delivery, and milestones) in children with ADHD and to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…In contrast to hard neurological signs localizable to a specific brain site, their soft counterparts are attributed to wider brain regions and functionally connected neuroanatomical systems, involved in integrative neurological functions such as sensory perception, coordination and motor sequencing [32], [33]. Neurological soft signs have been observed in a growing number of neuropsychiatric syndromes including mood disorders [34]–[36], obsessive-compulsive disorder (OCD) [37]–[39], post-traumatic stress disorder [26], [27], impulse control disorder [40], schizophrenia [32], [34], [41], and attention deficit hyperactivity disorder [42]. Furthermore, an inverse relationship between NSSs scores and total brain volume has been noted in psychopathological populations [27], [43] adding support to the generalized rather than localized NSSs' nature.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to hard neurological signs localizable to a specific brain site, their soft counterparts are attributed to wider brain regions and functionally connected neuroanatomical systems, involved in integrative neurological functions such as sensory perception, coordination and motor sequencing [32], [33]. Neurological soft signs have been observed in a growing number of neuropsychiatric syndromes including mood disorders [34]–[36], obsessive-compulsive disorder (OCD) [37]–[39], post-traumatic stress disorder [26], [27], impulse control disorder [40], schizophrenia [32], [34], [41], and attention deficit hyperactivity disorder [42]. Furthermore, an inverse relationship between NSSs scores and total brain volume has been noted in psychopathological populations [27], [43] adding support to the generalized rather than localized NSSs' nature.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors suggest that their presence beyond this age is indicative of some kind of maturational delay (Largo et al, 2001a,b). They are often found in patients suffering from mental disorders (Dazzan et al, 2008;Goswami et al, 2006;Negash et al, 2004;Zhao et al, 2013;Fountoulakis et al, 2017b;Panagiotidis et al, 2013), and also in children with ADHD (Patankar et al, 2012) or other developmental disorders (Dickstein et al, 2005;Szatmari and Taylor, 1984;Vitiello et al, 1990;Gottesman et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that poor coordination and impairments in fine and gross motor function are caused by difficulty in directing attention and by display of impulsive behavior [7, 8]. To date, motor function, including gait function, has been clinically assessed as a neurological soft sign in children with ADHD [9]. Gait function is one of the fundamental motor skills requiring both attention and executive function [7, 10].…”
Section: Introductionmentioning
confidence: 99%